A comparison of contrast sensitivity in early mild and early intermediate age-related macular degeneration after adjusting for age and visual acuity - Liutkevičienė, Rasa; Čiumbaraitė, Rasa; Banevičius, Mantas (Acta medica Lituanica, 2016)
Background. It has been suggested that contrast sensitivity can provide valuable information about visual function in addition to visual acuity assessment. Some patients retain relatively good visual acuity, yet complain of poor vision. In these patients, other tests of visual function such as contrast sensitivity should be evaluated. Methods. We examined patients with early mild stage age-related macular degeneration (group 1), and early intermediate stage age-related macular degeneration (group 2). Digital analysis methodology was used for retina drusen localisation and its diameter measurement. Functional acuity contrast sensitivity tests (FACT) were performed using a Ginsburg Box, VSCR-CST-6500. Results. The  nighttime results without glare in group  2 were worse at 1.5, 3, 6 and 18 cycles per degree of the visual angle, the daytime results without glare were worse at 3 and 6 cycles per degree. The nighttime results with glare were worse at 1.5, 3, 6 and 18 cycles per degree, and the daytime results with glare were worse at 1.5 and 3 cycles per degree. Results after adjusting for age and visual acuity to 1.0 in the  group 1  patients were better compared to the  group 2 patients and the p value was 0.0005. Conclusions. The  test results in patients with early intermediate age-related macular degeneration, in comparison to early mild age-related macular degeneration, showed a  significant decrease mostly in the nighttime either with or without glare in high and medium spatial frequencies (cycles/degree). After adjusting for age and visual acuity the FACT results were even worse in early intermediate AMD patients.